THE FUNCTIONS AND FORMS OF RODAT ART PRESENTATION IN KAMPUNG JAWA TONDANO (JATON) - Fafri Epafras Daniel Karundeng; Sri Sunarmi; Luccylle Takalumang (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This research aims to examine the functions and forms of Rodat art in Desa Kampung Jawa Tondano (Jaton), North Tondano District, Minahasa Regency. This research uses a descriptive qualitative approach with data collection methods through literature review, interviews, and document analysis. The research findings reveal the following aspects: First, the history of Rodat art in Jaton is closely related to the exile of Kiay Modjo and his friends who brought and taught traditional arts, including Rodat art. As a second point, Rodat art in Kampung Jawa Tondano has a service dimension for both private and public purposes, with individual tasks that include the fulfillment of material and psychological requirements. The religious, communicative, educational and recreational purposes of Rodat art in Jaton have significant relevance for the community. Third, the presentation structure of the Rodat art performance in Kampung Jawa Tondano involves elements such as presentation order, stage design, props, costumes, amplification, and lighting. The first recommendation is addressed to the Minahasa Regency Government, especially the Education Office, to include Rodat art in the school curriculum of Kampung Jawa Tondano. The second goal is to support the continuity of the Rodat art tradition in Kampung Jawa Tondano by inspiring the next generation to appreciate and practice this art.